Development of information and management competence of the heads of the structural unit of a modern university (Journal of Educational Sciences, 2021)
The relevance of the article is related to the need to introduce of innovations in the management of universities that ensure the quality of higher professional education. In turn, this implies the need for university managers to meet the professional requirements of modern management. The purpose of the article is: to describe the results of the study to identify effective conditions in the development of information and management competence of heads of structural divisions of a modern university. The methodological basis of the research is the result-oriented management methodology, the process-oriented approach, the systematic approach in management, as well as the provisions of the synergetic, acmeological, moderative and level approaches. In this article, the researchers described the features of the ascertaining stage of the experimental work, analyzed the general criteria of information and management competence, as well as the characteristics of modules aimed at developing information and management competence. The authors substantiate and describe the need to implement the formative stage of experimental work, taking into account the specially organized pedagogical influence within the framework of scientific approaches to the development of information and managerial competence of the heads of structural divisions of a modern university. The result of the research is a theoretical justification and experimental verification of the influence of the development of information and management competence of the heads of the university’s structural divisions on their successful activities in the management of a modern university. The scientific novelty lies in the fact that the conducted research contributes to the development of the theory of management, educational management, and the system of professional development of university managers. The practical significance of the article is related to the possibility of using the results of the study in improving the training of a new generation of higher school managers with a high level of professionalism, competence, and information and management culture. Key words: information competence, information and management competence of the head of the structural unit of the university, innovation, education manager.